Women’s Participation in Tourism Activities in Celuk Tourism Village, Gianyar Regency - Ayudia, Dewa Ayu Ratih Pradita; Prabawa, I Wayan Sukma Winarya; Lilasari, Luh Nyoman Tri (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
This research aims to determine the role of women in tourism activities in Celuk Tourism Village, Gianyar Regency. The qualitative method with a descriptive approach was method used in this research and in terms of data collection, applied mostly in interviews and observation. The results of this research show that the role of women in tourism activities in Celuk Tourism Village plays a role in three things, namely: Women’s participation in tourist attractions, tourist facilities and tourism organizations and they are played all in one as owners and managers. Challenges for women in roles include a lack of skills in technology, the younger generation of women who are less interested in silversmithing and multiple roles.